Pseudomonas aeruginosa Is More Tolerant Under Biofilm Than Under Planktonic Growth Conditions: A Multi-Isolate Survey - Thöming, Janne G.; Häussler, Susanne (Frontiers in Cellular and Infection Microbiology, 2022)
Biofilm-associated bacteria exhibit profound changes in bacterial physiology. They thrive in the environment but also in the human host in protected sessile communities. Antimicrobial therapy usually fails, despite the absence of genotypic resistance, and it is commonly accepted that biofilm-grown bacteria are up to 1,000 fold more resistant than planktonic cells. We are only at the beginning to understand the reasons for biofilm recalcitrance, and systematic approaches to describe biofilm-induced tolerance phenotypes are lacking. In this study, we investigated a large and highly diverse collection of 352 clinical Pseudomonas aeruginosa isolates for their antimicrobial susceptibility profiles under biofilm growth conditions towards the antibiotics ciprofloxacin, tobramycin, and colistin. We discovered characteristic patterns of drug-specific killing activity and detected conditional tolerance levels far lower (in the range of the minimal inhibitory concentration (MIC)), but also far higher (up to 16,000-fold increased compared to planktonic cells) than generally believed. This extremely broad distribution of biofilm-induced tolerance phenotypes across the clinical isolates was greatly influenced by the choice of the antibiotic. We furthermore describe cross-tolerance against ciprofloxacin and tobramycin, but not colistin, and observed an additive activity between biofilm-induced tolerance and genetically determined resistance. This became less evident when the biofilm-grown cells were exposed to very high antibiotic concentrations. Although much more remains be learned on the molecular mechanisms underlying biofilm-induced tolerance, our data on intra-species variations in tolerance profiles provide valuable new insights. Furthermore, our observation that colistin appears to act independently of the tolerance mechanisms of individual clinical strains could make colistin a valuable therapeutic option in chronic biofilm-associated infections characterized by the presence of particularly tolerant strains.